Die drei Ringe: Entstehung, Wandel und Wirkung der Ringparabel in der europäischen Literatur und Kultur - Aurnhammer, Achim; Cantarutti, Giulia; Vollhardt, Friedrich (Frühe Neuzeit, 2016)
"This volume aims to reconstruct the literary history of the compelling narrative model of the ring parable as a counterweight to contemporary reductionist misinterpretations, and to guide the reader through an archeology of European notions of tolerance. It traces the transformations of the parable from antiquity to Boccaccio, and then goes on to examine Lessing and modern reception."--